Pengaruh Jumlah Penduduk, Pengangguran, dan Pendidikan terhadap Kemiskinan di Wilayah Eks Karesidenan Banyumas - Imtihani, Evi; Syamsul Huda; Putra Perdana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Poverty is a condition characterized by insufficiency to satisfy everyday needs in situations not involving the will. Poverty can degrade the quality of human resources, resulting in lower levels of productivity and lower earnings. The aim of this study is to find out the influence of factors such as population, unemployment, and education on poverty in the Banyumas Ex-Resident Territory from 2013 to 2022. This is quantitative research, processing data using E-Views 10 software in the regression of panel data. The data used is secondary data from the Central Statistical Agency source. Fixed+Effect+Model became a suitable model in this study. According to the research, the population, unemployment, and education variables have a combined or simultaneous impact on the poverty variable.